2018
DOI: 10.5539/ibr.v11n2p44
|View full text |Cite
|
Sign up to set email alerts
|

The Policy Research for the Improvement of Excessive Marriage Expense in South Korea

Abstract: Excessive marriage-related expenses have become a serious social problem in South Korea. This has led to marriage delay, a low birthrate, the acceleration of an aging society, decreased national economic growth, and employment problems, among others. In South Korea, the young unmarried men and women cannot adequately prepare to shoulder the excessive expenses related to getting married in the future, as well as the high cost of purchasing a house. In fact, almost all of them are being supported by their parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The pooled analysis also indicated that parent homeownership is significant, increasing the risk of men's marriage by 27%. These findings confirm the importance of parental resources for men's marriage as housing remains a significant challenge to martial unions in East Asia (Deng et al, 2019; Lee, 2011; Raymo et al, 2015; Yoon, 2018; Zhang & Bian, 2021). The role of parental wealth in marriage outcomes seems to be indeed a defining feature of strong familism in Korea.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…The pooled analysis also indicated that parent homeownership is significant, increasing the risk of men's marriage by 27%. These findings confirm the importance of parental resources for men's marriage as housing remains a significant challenge to martial unions in East Asia (Deng et al, 2019; Lee, 2011; Raymo et al, 2015; Yoon, 2018; Zhang & Bian, 2021). The role of parental wealth in marriage outcomes seems to be indeed a defining feature of strong familism in Korea.…”
Section: Resultssupporting
confidence: 70%
“…Our study also helps clarify the unique challenges to marriage in strong familism societies. In Korea and several other comparable contexts, procuring the marital home is a significant hurdle given the “marriage package” defining the responsibilities for grooms and brides (Deng et al, 2019; Ji, 2015; Lee, 2011; Raymo et al, 2015; Yoon, 2018; Zhang & Bian, 2021). This burden is particularly pronounced when real estate market conditions are largely skewed toward home purchases and long‐term “key money” leases, rather than monthly rental properties (Kim, 2013; Ryu & Kim, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations